Performance and Energy Efficiency of Parallel Processing in a Multiprocessor System: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Performance of the multi-processor system analysed by them employed multitasking in case, there are fewer programs in the system requiring CPU service Than the number of CPUs. However, if there are alleast as many programs requiring CPU service as there are CPUs, then each CPU works on an independent program. In Their model, each program is broken up into two completely independent tasks when tv/o processors cooperate on a single program, A review of the work dona in the field of performance analysis of multiprocessor systems based on queueing models is contained in £ 110J, Sauer and Chancly have studied the behaviour of a multiprocessor system under various scheduling strategies and CPU service distributions.